The Influence of Environmental, Social, and Governance (ESG) Disclosure, Profitability, Leverage, and Capital Intensity on Tax Avoidance in Manufacturing Companies during The 2021-2023 Period - Zahra, Maulida Rozana (DIPONEGORO UNIVERSITY, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure, profitability, leverage, and capital intensity on tax avoidance. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The dependent variable in this study is tax avoidance, measured using the Cash Effective Tax Rate (CETR), while the independent variables consist of ESG disclosure, Return on Assets (ROA) for profitability, Debt to Asset Ratio (DAR) for leverage, and Capital Intensity Ratio (CIR).This research employs a quantitative method with an associative approach. Data were collected through documentation of secondary data obtained from the Bloomberg database. The sample was selected using purposive sampling, resulting in 136 observational data after removing outliers. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics 26, along with classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests.The results of the study indicate that ESG disclosure, profitability, leverage, and capital intensity simultaneously have a significant effect on tax avoidance. Partially, ESG disclosure has a significant positive effect on tax avoidance, while capital intensity has a significant negative effect. Meanwhile, profitability and leverage have no significant effect on tax avoidance.